French Literature : A Very Short Introduction - Lyons, John D. (Oxford Oxford University Press, 2010)
The heritage of literature in the French language is rich, varied, and extensive in time and space. This Very Short Introduction presents this lively literary world by focusing on texts (epics, novels, plays, poems, screenplays) that concern protagonists whose adventures and conflicts reveal shifts in literary and social practices.
Include Illustrations and Index.
A Very Short Introduction.
Keywords: French Literature -- Literature - French